How to Determine Deposit Insurance Premium: A Book Value Approach - S. K. Asnawi (Финансы: теория и практика)
The purpose of the study is to propose a new model for determining insurance premiums on deposits. As of today, there are two models: the first is theoretical, using market value (option theory), and the second is practical, using book value and, as a rule, a fixed rate. Market value cannot be applied as it does not reflect banking risk, while the use of book value is considered mandatory without any theoretical justification.This paper proposes a new model, namely the Asnawi Model with three advantages, namely: (1) based on book value, (2) considering the bank’s risk-return (fair premium); and (3) considering incentive-compatible plans. The model formation is based on the main variables that influence banking performance, namely (1) asset-to-deposit ratio (2) lending-borrowing rate ratio, (3) and non-performing loans.The results of this research are: first, the formation of four Asnawi Groups which indicate the amount of premium that must be paid by the bank (group 4 is the one with the lowest premium); second, the Asnawi Score, as a reference value for banks to get/not get incentives; third, the results of simulations on Indonesian banking showed variations in premium groups, and in the fourth, regression of the three variables above on ROE, the results were found to be in line with predictions. This model for determining insurance premiums can be a reference/alternative for determining premiums in worldwide banks.